If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + 11 = 12x + -7 Reorder the terms: 11 + 8x = 12x + -7 Reorder the terms: 11 + 8x = -7 + 12x Solving 11 + 8x = -7 + 12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12x' to each side of the equation. 11 + 8x + -12x = -7 + 12x + -12x Combine like terms: 8x + -12x = -4x 11 + -4x = -7 + 12x + -12x Combine like terms: 12x + -12x = 0 11 + -4x = -7 + 0 11 + -4x = -7 Add '-11' to each side of the equation. 11 + -11 + -4x = -7 + -11 Combine like terms: 11 + -11 = 0 0 + -4x = -7 + -11 -4x = -7 + -11 Combine like terms: -7 + -11 = -18 -4x = -18 Divide each side by '-4'. x = 4.5 Simplifying x = 4.5
| -5=4(2+9r)-5r | | 0.13y+0.08(y+9000)=2400 | | 4(-6p+2)=9p-1 | | -t+4=13 | | 4a+5=35 | | 5ln(x+4)-17=8 | | 12ab+6ab-9bc= | | 3x-16=4-2x | | 48s-34=48-28s | | 10-7=63 | | 51x-7=34x+163 | | .06x+x=5000 | | 3(4x)=27 | | 35-10= | | (x+5)(x+7)=105 | | sin(2x)=cos(5x) | | b^2-3=6 | | Y=9x-4xy+2x-xy | | 5r^2=10 | | 4y+20=15y-24 | | 3*ln(x+2)=9 | | 112+13p=86 | | 5x-16=x | | 5y-7=y+3 | | 4x-18=17+5 | | 56-6x=-28+8x | | 2x^2+8x-26=0 | | 5q^3(q^4-6q)= | | 96x+51y=6 | | ((6n^3)/(7x^5*y^2))/((3mn^20/(21x^3*y)) | | n/3=2n/6 | | 2x^2+4y=6 |